Profiling of plasma extracellular vesicles identifies proteins that strongly associate with patient’s global assessment of disease activity in rheumatoid arthritis - Arntz, Onno J.; Thurlings, Rogier M.; Blaney Davidson, Esmeralda N.; Jansen, Pascal W. T. C.; Vermeulen, Michiel; Koenders, Marije I.; van der Kraan, Peter M.; van de Loo, Fons A. J. (Frontiers in Medicine, 2024)
Background Rheumatoid arthritis (RA) is an autoimmune disease characterized by chronic synovial inflammation and cartilage/bone damage. Intercellular messengers such as IL-1 and TNF play a crucial role in the pathophysiology of RA but have limited diagnostic and prognostic values. Therefore, we assessed whether the protein content of the recently discovered extracellular vesicles (EVs), which have gained attention in the pathogenesis of RA, correlates with disease activity parameters in RA patients. Methods We identified and quantified proteins in plasma-derived EVs (pEVs), isolated by size exclusion chromatography from 17 RA patients by mass spectrophotometry (MS). Quantified protein levels were correlated with laboratory and clinical parameters and the patient’s own global assessment of their disease activity (PGA-VAS). In a second MS run, the pEV proteins of nine other RA patients were quantified and compared to those from nine healthy controls (HC). Results No differences were observed in the concentration, size, and protein content of pEVs from RA patients. Proteomics revealed >95% overlapping proteins in RA-pEVs, compared to HC-pEVs (data are available via ProteomeXchange with identifier PXD046058). Remarkably, in both runs, the level of far more RA-pEV proteins correlated positively to PGA-VAS than to either clinical or laboratory parameters. Interestingly, all observed PGA-VAS positively correlated RA-pEV proteins were associated with the actin-cytoskeleton linker proteins, ezrin, and moesin. Conclusion Our observation suggests that PGA-VAS (loss of vitality) may have a different underlying pathological mechanism in RA, possibly related to enhanced muscle actin-cytoskeleton activity. Furthermore, our study contributes to the growing awareness and evidence that pEVs contain valuable biomarkers for diseases, with added value for RA patients.